Sexual dimorphism alters seasonal chelae muscle mechanisms in spiny-cheek crayfish (Faxonius limosus) - Śmietana, Przemysław; Śmietana, Natalia; Eljasik, Piotr; Lisiecki, Sławomir; Sobczak, Małgorzata; Panicz, Remigiusz (Frontiers in Physiology, 2025)
Sex-specific behaviours of freshwater crayfish are key elements in sustaining species persistence and successful conquering of new habitats in freshwater ecosystems. However, to date, information on molecular mechanisms that underpin the anatomy and physiology of crayfish sexes in successful mating behaviour was scarcely presented. In this study, Faxonius limosus females and males were sampled in spring and autumn to assess the impact of sexes and seasons on body parameters and activity of arginine kinase (ak), ferritin (fr), crustacean calcium-binding protein 23 (ccbp-23), troponin c (tnnc), and skeletal muscle actin 8 (actinsk8) genes related to the functioning of muscles in chelae. Comparison of body parameters showed significant differences in the weight and size of individuals in two seasons, underlining that large chelae are essential for males in mating behaviours and male-male competitive interactions. The gene expression analysis showed that activities of the five genes in the chelae muscle of F. limosus were influenced by the season- and sex-specific drivers. Multivariate analyses specifically identified the key genes (e.g., tnnc in males from spring) that were directly involved in metabolisms of chelae muscles of males and females collected in spring and autumn. The study, for the first time, described the direct impact of two key seasons and sexes on the anatomical features and molecular mechanisms that shaped the behaviour of F. limosus.